Optical observations of the broad-lined type Ic supernova SN 2012ap. (1st February 2015) - Liu, Zheng; Zhao, Xu-Lin; Huang, Fang; Wang, Xiao-Feng; Zhang, Tian-Meng; Chen, Jun-Cheng; Zhang, Tong-Jie
Abstract The optical observations of the type Ic supernova (SN Ic) SN 2012ap in NGC 1729 are presented. A comparison with other SNe Ic indicates that SN 2012ap is highly reddened (with E(B — V)host∼0.8 mag) and may represent one of the most luminous SNe Ic ever observed, with an absolute V-band peak magnitude of ∼ −19.3±0.5 mag after extinction correction. The near-maximum-light spectrum shows wide spectral features that are typical of broad-lined SNe Ic. One interesting feature in the spectrum is the appearance of some narrow absorption features that can be attributed to the diffuse interstellar bands, consistent with the large reddening inferred from the photometric method. Based on the light curves and the spectral data, we estimate that SN 2012ap produced a 56Ni mass of ∼ 0.3 ± 0.1M⊙ 1 in the explosion, with an ejecta mass of 2.4−0.7+0.7M⊙ and a kinetic energy of EK = 1.1−0.4+0.4 × 1052 erg. The properties of its progenitor are also briefly discussed.